Community Pharmacies Behind the Scenes - Mustafa Targhi,; Wadiaa Benamer,; Tamader Elghnimi,; Mohamed Hussiny,; Abd Allah Mashmmor, (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Pharmacists are patient centered health care providers who are educated to advice and fulfill many of patient's health care and drug needs. However, lately this profession has been violated by many non-pharmacist intruders who practiced as pharmacists. This study is the first and the only one carried out in Libya up to this time, to find out who actually are running the pharmacies and their level of knowledge on some basic pharmacy background information, and technical terms that are unique to pharmacy education, elements of dispensing and the concept of pharmaceutical care with its communication and counseling aspects. Methods. Field visits to a total of 200 pharmacies across greater Tripoli city were carried out, along with interviews of the dispensing personnel, using questionnaire form to evaluate their level of knowledge on some of the basic information and technical terms that are unique to pharmacy education, in addition to elements of dispensing and the concept of pharmaceutical care with its communication and counseling aspects. Results. The results showed that of the personnel running the pharmacies, pharmacists represented only about 30%, assistant pharmacists about 10%, medical professions (physicians, dentists, veterinarians, medical technologists and nurses) about 50%, in addition non-health related profession 10% (teachers, engineers, accountant, agriculturist engineers…etc). Moreover, the intruders have very little information, if not at all, on the elements of good dispensing practice. Conclusion. It is highly recommended that the relevant authority bodies (pharmacists' syndicate, association of pharmacists and ministry of health) not only set regulations to protect this profession but also to enforce them for urgent implementation.